2002
DOI: 10.1046/j.1442-2050.2002.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse esophageal leiomyomatosis with localized dense eosinophilic infiltration

Abstract: Diffuse esophageal leiomyomatosis is a rare cause of dysphagia. There is frequently a chronic inflammatory infiltrate, but here we present the first reported case in association with a dense infiltration of eosinophils and mast cells confined to the affected muscularis propria. This was successfully managed by long esophageal myotomy, with resolution of dysphagia and no symptomatic recurrence after 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
(12 reference statements)
1
7
0
Order By: Relevance
“…One patient's symptoms spontaneously resolved while another was helped by myotomy. 10 Patients who previously showed improvement in symptoms with steroids and those with poor relief from other regimens were commenced on Montelukast in an attempt at symptom control without the need for long term corticosteroid therapy.…”
Section: Methodsmentioning
confidence: 99%
“…One patient's symptoms spontaneously resolved while another was helped by myotomy. 10 Patients who previously showed improvement in symptoms with steroids and those with poor relief from other regimens were commenced on Montelukast in an attempt at symptom control without the need for long term corticosteroid therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Patients may be asymptomatic at presentation or complain of pain, dysphagia, and weight loss 1–3 . Infiltration of leiomyomas by hematopoietic elements is rare and has only been previously reported in the uterus and in diffuse esophageal leiomyomatosis in association with allergic conditions and idiopathic eosinophilic esophagitis 4–6 . To the best of our knowledge, this is the first report of a patient with a solitary esophageal leiomyoma containing a prominent eosinophilic infiltrate in the absence of allergy and eosinophilic esophagitis.…”
mentioning
confidence: 88%
“…Hematopoietic infiltration, including lymphocytes, mast cells, histiocytes, and extramedullary hematopoiesis of leiomyomata is rare and has been reported in leiomyomata of the uterus and in diffuse esophageal leiomyomatosis 4,6 . When eosinophilic infiltration is present, the eosinophils represent a minor component of the inflammatory infiltrate and demonstrate an angiocentric distribution 4–6 . Nicholson et al .…”
Section: Commentmentioning
confidence: 99%
“…However, functional causes of dysphagia should be excluded by manometry and pH studies. Morris et al 11 reported the first case of diffuse leiomyomatosis with dense eosinophilic infiltration. Eosinophils represent a minor component of inflammatory infiltrate with angiocentric distribution.…”
Section: Discussionmentioning
confidence: 99%